CD147-high classical monocytes: a cellular biomarker for COVID-19 disease severity and treatment response - Teruaki Murakami; Yuta Yamaguchi; Saori Amiya; Yuko Yoshimine; Shinichiro Nameki; Yasutaka Okita; Yasuhiro Kato; Haruhiko Hirata; Yoshito Takeda; Atsushi Kumanogoh; Takayoshi Morita (Inflammation and Regeneration)
Abstract Background Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection can lead to severe coronavirus disease 2019 (COVID-19), which is characterized by cytokine storm and organ dysfunction. The spike S1 subunit induces inflammatory cytokine production, but the immune cell subsets that respond to S1 stimulation and contribute to disease severity remain unclear. Methods We analyzed serum samples and peripheral blood mononuclear cells (PBMCs) from patients with COVID-19 (moderate: n = 7; severe: n = 25) and healthy controls (n = 38). Using mass cytometry (cytometry by time-of-flight; CyTOF), we analyzed immune cell responses to S1 subunit stimulation in PBMCs from healthy donors and patients with COVID-19. We examined correlations among identified cell populations, serum cytokine levels, and clinical parameters. Results Serum S1 subunit levels correlated with disease severity and inflammatory cytokine concentrations. S1 subunit stimulation induced dose-dependent cytokine production from PBMCs, predominantly from myeloid cells. CyTOF analysis identified classical monocytes with high CD147 expression (CD147hi cMono) as the primary source of S1-induced cytokines. The proportion of CD147hi cMono increased significantly in severe COVID-19 and decreased with clinical improvement. The frequency of CD147hi cMono showed a stronger positive correlation with clinical severity markers in younger patients compared to older patients. Conclusions CD147hi cMono are the primary cellular source of S1-induced inflammatory cytokines and may serve as potential biomarkers for monitoring COVID-19 severity and treatment response.